The knowledge of lexical collocation among university students and its relation to their speaking proficiency - Abdul Ghani, Rozina (SCIPRESS, 2015)

(untitled)
ABSTRACT This study aims to investigate students’ collocational competence by examining the relationship between the knowledge of lexical collocation among them. The respondents were 30 students of Universiti Malaysia Kelantan (UMK). A lexical collocation test (LCT) was constructed to gauge the knowledge of collocation, while a speaking proficiency test (SPT) adopted from the IELTS was administered to determine the students’ level of speaking proficiency. Both variables were then correlated. The result indicates that there was no significant correlation between the knowledge of collocation and speaking proficiency among the respondents. Based on the findings, it is revealed that exposure to the target language plays a vital role in language acquisition. Exposure to collocations in particular would enable the learners to speak more fluently and sound more native-like.